Treadmill Exercise Ameliorates Depression-Like Behavior in the Rats With Prenatal Dexamethasone Exposure: The Role of Hippocampal Mitochondria - Wu, Tianwen; Huang, Yan; Gong, Yuxiang; Xu, Yongjun; Lu, Jianqiang; Sheng, Hui; Ni, Xin (Frontiers in Neuroscience, 2019)
Abstract Prenatal exposure to synthetic glucocorticoids (sGCs) can increase the risk of affective disorders, such as depression, in adulthood. Given that exercise training can ameliorate depression and improve mitochondrial function, we sought to investigate whether exercise can ameliorate depression-like behavior induced by prenatal sGC exposure and mitochondria function contributes to that behavior. At first, we confirmed that prenatal dexamethasone (Dex) administration in late pregnancy resulted in depression-like behavior and elevated level of circulatory corticosterone in adult offspring. We then found that mRNA and protein expression of a number of mitochondrial genes was changed in the hippocampus of Dex offspring. Mitochondria in the hippocampus showed abnormal morphology, oxidative stress and dysfunction in Dex offspring. Intracerebroventricular (ICV) injection of the mitochondrial superoxide scavenger mitoTEMPO significantly alleviated depression-like behavior but did not significantly affect circulatory corticosterone level in Dex offspring. The adult Dex offspring treated with treadmill exercise starting at four-weeks of age showed ameliorated depressive-like behavior, improved mitochondrial morphology and function and reduced circulatory corticosterone level. Our data suggest mitochondria dysfunction contributes to depression-like behavior caused by prenatal sGC exposure. Intervention with exercise training in early life can reverse depression caused by prenatal Dex exposure, which is associated with improvement of mitochondrial function in the hippocampus. Key Words: depression, hippocampus, glucocorticoid, mitochondria, exercise